ANALYSIS OF MURABAHA FINANCING SYSTEMS AND PROCEDURES IN KPRS PRODUCTS AT BTN SYARIAH KCPS CIBINONG - Rizqiana, Sayekti; Mukri, Syarifah Gustiawati; Hakim, Nurman (MIZAN: JOURNAL OF ISLAMIC LAW, 2023)
BTN Syariah can conduct KPRS financing through a murabahah (sale-purchase) agreement in a mutually agreed agreement. This research aims to find out how the system and procedure of KPRS financing at BTN Syariah KCPS Cibinong and to find out whether the application of murabahah financing in KPRS products at BTNS KCPS Cibinong is based on the provisions of Fatwa DSN MUI No: 04/DSN-MUI/IV/2000. The type of research used is descriptive qualitative research that can describe or provide an overview of a phenomenon or event in the problems that occur at BTN Syariah KCPS Cibinong from the results of interviews, objects and documentation how researchers can explain the problems that will be discussed in this thesis. The results of this study indicate that the application of the KPRS financing system and procedures at BTN Syariah KCPS is in accordance with the BTN Syariah company SOP and must be carried out because there are already provisions from BTN Syariah and the application of murabaha financing in KPRS products at BTN Syariah KCPS Cibinong is in accordance with the DSN MUI fatwa No: 04/DSN-MUI/IV/2000.